1982
DOI: 10.1007/bf01318081
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of bovid herpesvirus 2 replication to temperatures found in the natural host

Abstract: Two isolates of bovid herpesvirus 2 replicated poorly in bovine testicular cells and fetal kidney cells at 39--40 degrees C, temperatures commonly observed in virus-infected cattle. High viral titers occurred in replicate cultures at 30--37 degrees C. Persistent viral infections were noted in cultures maintained at 40 degrees C. Interferon-like activity was not responsible for the high-temperature restriction since the level was not significantly different between virus-infected cultures incubated at 35 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In contrast, virus inoculation after skin scarification did not result in viremic spread in spite of virus replication and detection in local sites for 4 to 6 days (Table 1). The localized nature of cutaneous BoHV-2 replication and pathology has been previously attributed to the route of virus penetration/exposure, specific virus tropism and, additionally, to the surface temperature which may favor virus replication (Letchworth et al 1982a). In fact, early studies have demonstrated that BoHV-2 replicates more efficiently at lower temperatures (30-3 o C), comparing to replication at physiological bovine temperatures (38-39 o C) (Letchworth et al 1982a, Letchworth & Carmichael 1984.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, virus inoculation after skin scarification did not result in viremic spread in spite of virus replication and detection in local sites for 4 to 6 days (Table 1). The localized nature of cutaneous BoHV-2 replication and pathology has been previously attributed to the route of virus penetration/exposure, specific virus tropism and, additionally, to the surface temperature which may favor virus replication (Letchworth et al 1982a). In fact, early studies have demonstrated that BoHV-2 replicates more efficiently at lower temperatures (30-3 o C), comparing to replication at physiological bovine temperatures (38-39 o C) (Letchworth et al 1982a, Letchworth & Carmichael 1984.…”
Section: Discussionmentioning
confidence: 99%
“…The localized nature of cutaneous BoHV-2 replication and pathology has been previously attributed to the route of virus penetration/exposure, specific virus tropism and, additionally, to the surface temperature which may favor virus replication (Letchworth et al 1982a). In fact, early studies have demonstrated that BoHV-2 replicates more efficiently at lower temperatures (30-3 o C), comparing to replication at physiological bovine temperatures (38-39 o C) (Letchworth et al 1982a, Letchworth & Carmichael 1984. The preference for replication at low temperatures might also explain the higher incidence and distribution of BoHV-2 in regions of temperate climate (Letchworth & Carmichael 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Virus-induced lesions are usually restricted to the skin of the udder and teats (18) despite the presence of virus in internal tissues (5) and the ability of this virus to replicate to high titers in bovine internal organ tissues in vitro (5, 6, 19,22,25). Growth in vitro of BHV-2 is strongly restricted by the 40 to 41°C temperatures often found in BHV-2infected cattle (5, 7,8,11,23), but the virus replicates to high titers at the lower temperatures (30 to 37°C) characteristic of bovine skin (13). Bovine cells produce interferon in response to BHV-2 infection, but the ability of that interferon to restrict BHV-2 growth in bovine cells is dependent on temperatures usually encountered internally in cattle (35 to 40°C) (G. J. Letchworth and L. E. Carmichael, submitted for publication).…”
mentioning
confidence: 99%